HUBUNGAN DUKUNGAN SOSIAL DAN KONFLIK PERAN DENGAN BURNOUT PADA PERAWAT DI RUMAH SAKIT JIWA PROVINSI SULAWESI TENGGARA TAHUN 2021 - Anisa Ninuk Melania; Jafriati Jafriati; Asnia Zainuddin (FKM Universitas Halu Oleo, 2022)
Burnout is an occupational health and work productivity problem with an increasing prevalence, almost half of the total number of workers experiencing burnout are nurses. Burnout syndrome is fatigue physically, emotionally and mentally due to being in an emotionally demanding situation that can cause a change in attitudes and behavior. The aim of this research is to find out the relationship between social support and role conflict with Burnout in nurses at the Mental Hospital of Southeast Sulawesi Province in 2021. This type of research is an analytical observational study with a Cross Sectional. The sampling technique in this study used Total Sampling. The results of this study indicate that instrumental support (p value = 0.019), emotional support (p value = 0.005), appreciation support (p value = 0.003) and role conflict (p value = 0.037) have a relationship with burnout in nurses at the Sulawesi Provincial HospitalSoutheast Sulawesi, while informative support (p value = 0.684) did not have a relationship with burnout among nurses at the Southeast Sulawesi Provincial Hospital. The results of this study can be concluded that those related to burnout in nurses in the Southeast Sulawesi Provincial Hospital are instrumental support, emotional support, appreciation support and role conflict